Wireless Network Planning and Optimization in Oil and Gas Refineries - Savazzi, Stefano; Souza, Ramon Hugo de; Becker, Leandro Buss (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2013)
The widespread adoption of wireless systems forindustrial automation calls for the development of efficient tools for virtual planning of network deployments similarly as done for conventional Field bus and wired systems. In industrial sites the radio signal propagation is subject to blockage due to highly dense metallic structures. Network planning should therefore account for the number and the density of the 3D obstructions surrounding each link. In this paper we address the problem of wireless node deployment in wireless industrial networks, with special focus on WirelessHART IEC 62591 and ISA IEC 62734 standards. The goal is to optimize the network connectivity and provide practical deployment rules in complex industrial sites characterized by severe obstructions. The proposed node deployment approach is validated through a case study in an oil refinery environment. It includes an ad-hoc simulation environment that implements the proposed network planning approach using 2D models of the plant, providing connectivity information based on user-defined deployment configurations. Obtained results were validated by on-site measurements.